2018
DOI: 10.1016/j.jprot.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in cardiovascular diseases: Unveiling sex and gender differences in the era of precision medicine

Abstract: Increasing evidence supports the profound effect of sex and gender on cardiovascular physio-pathology and the response to drugs. A clear understanding of the mechanisms underlying sexual dimorphisms in CVDs would not only improve our knowledge of the etiology of these diseases, but could also inform health policy makers and guideline committees in tailoring specific interventions for the prevention, treatment and management of CVDs in both men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 167 publications
0
18
0
Order By: Relevance
“…In the same fashion, the complex cascade mediated by estrogen may lead to changes in coagulation and other systems, accounting for the key role of sex hormone fluctuations in establishing CVD risk, including those occurring during menopause and pregnancy [39,62]. A recent study by Baetta and co-workers [37] clearly reviewed the current status of studies investigating the molecular basis of sex differences in CVD, mainly through the proteomic approach. In this regard, studies on the circulating levels of potential soluble CVD markers have revealed sex-specific differences, such as those in serum levels of the adipocyte fatty acid-binding protein (A-FABP), emerging as a relevant atherosclerosis marker in women (i.e., with different fat distribution and hormonal regulation compared to men), supporting the need for sex/gender-specific biomarkers to be translated in clinical practice [63,64].…”
Section: Women-specific Cvd Risk Factors and Their Molecular Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same fashion, the complex cascade mediated by estrogen may lead to changes in coagulation and other systems, accounting for the key role of sex hormone fluctuations in establishing CVD risk, including those occurring during menopause and pregnancy [39,62]. A recent study by Baetta and co-workers [37] clearly reviewed the current status of studies investigating the molecular basis of sex differences in CVD, mainly through the proteomic approach. In this regard, studies on the circulating levels of potential soluble CVD markers have revealed sex-specific differences, such as those in serum levels of the adipocyte fatty acid-binding protein (A-FABP), emerging as a relevant atherosclerosis marker in women (i.e., with different fat distribution and hormonal regulation compared to men), supporting the need for sex/gender-specific biomarkers to be translated in clinical practice [63,64].…”
Section: Women-specific Cvd Risk Factors and Their Molecular Mechanismmentioning
confidence: 99%
“…Studies aimed at precision medicine are providing increasing data highlighting that it is indeed no longer possible to avoid a proper consideration of sex/gender differences when approaching disease pathophysiology [36][37][38]. Environmental, social, and psychological differences can contribute to sex/gender imbalances in CVD.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have used proteomics to investigate sex differences and overall CVD risk, mostly from biological fluids, such as plasma/serum and urine. 69 In parallel, advancements in the proteomic profiling of atherosclerotic tissue have also occurred. 62 However, as aptly reviewed, studies have yet to focus on identifying sex differences in the atherosclerotic plaque tissue proteome, until "now" (Paper I).…”
Section: "Proteins Are Central To Our Understanding Of Cellular Functmentioning
confidence: 99%
“…62 However, as aptly reviewed, studies have yet to focus on identifying sex differences in the atherosclerotic plaque tissue proteome, until "now" (Paper I). 69…”
Section: "Proteins Are Central To Our Understanding Of Cellular Functmentioning
confidence: 99%
“…28 Many studies have demonstrated a gender difference in clinical presentations, diagnosis, treatment, and prevention. 29 Sadly, many women may not always understand the caution and indication signs of a cardiac arrest. An analysis was performed on 515 women patients who experienced an episode or more heart failures disclosed that approximately 43% had not experienced any type of classic signs such as palpitation, arrhythmias, chest pain, shortness of breath, or pressure during the heart attack.…”
Section: Introductionmentioning
confidence: 99%